2020
DOI: 10.3389/fchem.2020.552795
|View full text |Cite
|
Sign up to set email alerts
|

In-situ Formation of Amorphous Co-Al-P Layer on CoAl Layered Double Hydroxide Nanoarray as Neutral Electrocatalysts for Hydrogen Evolution Reaction

Abstract: Exploration of high-efficiency and inexpensive electrode catalysts is of vital importance for the hydrogen evolution reaction (HER). In this research, an amorphous CoAl -P layer was constructed on the surface of CoAl layered double hydroxide (CoAl-LDH) via an in-situ wet phosphidation strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…It can be observed that the nanolayer was nicely orientated along the <01-11> zone axis and the analysis provided interplanar distances of 0.14 nm, 0.19 nm and 0.25 nm ascribed to (110), ( 112) and (102) planes, respectively. These values were consistent with those reported in the literature [78,79]. Selected area electron diffraction (SAED) pattern involving many of these nanosheets, shown at the bottom-left inset Figure 5a.…”
Section: Resultssupporting
confidence: 91%
“…It can be observed that the nanolayer was nicely orientated along the <01-11> zone axis and the analysis provided interplanar distances of 0.14 nm, 0.19 nm and 0.25 nm ascribed to (110), ( 112) and (102) planes, respectively. These values were consistent with those reported in the literature [78,79]. Selected area electron diffraction (SAED) pattern involving many of these nanosheets, shown at the bottom-left inset Figure 5a.…”
Section: Resultssupporting
confidence: 91%
“…Figure S1 exhibited the XRD spectra of USY zeolite and CoAl‐LDH@USY precursor. Compared with USY, additional characteristic diffraction peaks at 11.5°, 34.6°, and 60.0° which were attributed to the formation of CoAl‐LDH were observed in CoAl‐LDH@USY, and the structure of USY was retained after in‐situ growth, suggesting the formation of CoAl‐LDH on USY surface [25] . Figure 1(b) showed the XRD patterns of the Co‐based catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with USY, additional characteristic diffraction peaks at 11.5°, 34.6°, and 60.0°which were attributed to the formation of CoAl-LDH were observed in CoAl-LDH@USY, and the structure of USY was retained after in-situ growth, suggesting the formation of CoAl-LDH on USY surface. [25] ChemCatChem lattice planes of Co (JCPDS 05-0527). The results indicated that Co nanoparticles were successfully formed on the catalysts.…”
Section: Characterizationmentioning
confidence: 99%
“…On the other hand, some noble metal-free based and carbon-loaded transition metal electrocatalysts for chlorine evolution have been developed, but their catalytic efficiency and durability still cannot meet the requirements. Amorphous alloys, due to their unique disordered structure, surface inhomogeneity, and wide compositional adjustability range, have been proved to have excellent performance in catalytic processes such as hydrogen and oxygen evolution. In the chlorine evolution reaction, amorphous alloys also have great catalytic potential. However, amorphous alloys have a complicated compositional space; just take a simple binary alloy as an example, there are 10 15 compositional schemes for clusters of 150 atoms, which have caused a great obstacle for researchers to explore the catalytic mechanism of chlorine evolution in amorphous alloys.…”
Section: Introductionmentioning
confidence: 99%